The Important Of Digital Accounting And Indonesian Government Incentives In Strengthening MSMEs’ Performance During the COVID-19 Pandemic - Apriyanti, Hani Werdi; Budiman, Judi (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2023)
Purpose: This paper provides a discussion of how financial access, tax incentives, MSMEs’ social assistance programs, accounting skills, and digital accounting utilization affects the MSMEs’ performance, during the COVID-19 pandemicMethod: The data was generated by a questionnaire sent to the food and beverage MSME sector in Semarang City, Central Java, Indonesia. The population in this study was 17.602 MSME in Semarang City, Central Java, Indonesia. The sample was 261 MSMEs in the food and beverage MSMEs sector obtained using a convenience sampling technique. Descriptive statistics, data quality tests, classic assumption tests, regression analyses, and hypotheses were tested with SPSS 25 software. Findings: Based on the hypotheses tests, the results show that accounting skills, digital accounting, and financial access have a significant positive effect on MSMEs’ Performance during Pandemic COVID-19 in Semarang. While tax incentives and MSMEs’ social assistance programs do not affect on MSMEs’ performance during the pandemic.Novelty: This study provides a unique detailed examination of actual practice and an indication of the future trend in digital accounting for MSMEs, and the role of government incentives to assist the MSME’s performance during the pandemic.